2022
DOI: 10.26740/jpak.v10n2.p138-151
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Pembelajaran Akuntansi Berbasis Android “LAKEUN” Pada Materi Laporan Keuangan Perusahaan Dagang Kelas XI Akuntansi SMKN 6 Surabaya

Abstract: The development of science and technology has an impact on teaching and learning activities. Educators are required to make teaching and learning activities more varied so that students can play an active role during teaching and learning activities. Learning media can be an alternative for educators to create student participation during teaching and learning activities. Based on observations made by researchers, it was found that the media that had been used by accounting teachers at SMKN 6 Surabaya, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…Karena berdasarkan hasil pengamatan guru hanya menggunakan satu sumber yaitu buku cetak, buku yang digunakan menggunakan bahasa yang sulit dipahami oleh peserta didik, sehingga minat belajar peserta didik menurun. Menurut Manasikana & Listiadi (2017) menegaskan bahwa penggunaan bahan ajar yang sesuai dapat meningkatkan efektivitas dan efisiensi pembelajaran, serta mendorong siswa untuk belajar mandiri.…”
Section: Analisis (Analyze)unclassified
“…Karena berdasarkan hasil pengamatan guru hanya menggunakan satu sumber yaitu buku cetak, buku yang digunakan menggunakan bahasa yang sulit dipahami oleh peserta didik, sehingga minat belajar peserta didik menurun. Menurut Manasikana & Listiadi (2017) menegaskan bahwa penggunaan bahan ajar yang sesuai dapat meningkatkan efektivitas dan efisiensi pembelajaran, serta mendorong siswa untuk belajar mandiri.…”
Section: Analisis (Analyze)unclassified
“…At this stage the android-based accounting learning media product was tested on one, tested on three students at SMK Negeri 8 Palembang who had low, medium and above average abilities. Students learn using Android-based accounting learning media, after which the researcher conducts interviews with students to provide comments or suggestions on the teaching materials that have been developed (Zaman & Listiadi, 2022). Based on the results of the comments of 3 students involved in the one-on-one trial, it can be concluded that Android -based accounting learning media can attract students' interest in learning.…”
Section: Evaluate the Onementioning
confidence: 99%
“…Salah satu bentuk inovasi dalam bidang pendidikan adalah menciptakan bahan ajar yang bersifat interaktif. Bahan ajar tersebut merupakan materi berbasis digital yang menggabungkan berbagai jenis media, termasuk audio, text, graphics, images, dan animation (Manasikana & Listiadi, 2017). Bahan ajar berbasis digital merupakan sumber belajar yang membantu peserta didik memiliki pengalaman belajar yang konkrit, kontekstual, interaktif, dan adaptif sejalan dengan ilmu dan pengetahuan teknologi (Santi et al, 2023).…”
Section: Pendahuluanunclassified